Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Sure, let's solve the quadratic equation step by step using the quadratic formula.
The given quadratic equation is [tex]\(3x^2 - x - 10 = 0\)[/tex].
For a quadratic equation of the form [tex]\(ax^2 + bx + c = 0\)[/tex], the quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, we have:
- [tex]\(a = 3\)[/tex]
- [tex]\(b = -1\)[/tex]
- [tex]\(c = -10\)[/tex]
Let's first calculate the discriminant, [tex]\(\Delta\)[/tex], which is given by:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \Delta = (-1)^2 - 4(3)(-10) \][/tex]
[tex]\[ \Delta = 1 - (-120) \][/tex]
[tex]\[ \Delta = 1 + 120 \][/tex]
[tex]\[ \Delta = 121 \][/tex]
Now, we'll calculate the two solutions using the quadratic formula:
[tex]\[ x_1 = \frac{-b + \sqrt{\Delta}}{2a} \][/tex]
[tex]\[ x_2 = \frac{-b - \sqrt{\Delta}}{2a} \][/tex]
Substituting the values:
[tex]\[ x_1 = \frac{-(-1) + \sqrt{121}}{2 \cdot 3} \][/tex]
[tex]\[ x_1 = \frac{1 + 11}{6} \][/tex]
[tex]\[ x_1 = \frac{12}{6} \][/tex]
[tex]\[ x_1 = 2 \][/tex]
And for the second solution:
[tex]\[ x_2 = \frac{-(-1) - \sqrt{121}}{2 \cdot 3} \][/tex]
[tex]\[ x_2 = \frac{1 - 11}{6} \][/tex]
[tex]\[ x_2 = \frac{-10}{6} \][/tex]
[tex]\[ x_2 = -\frac{10}{6} \][/tex]
[tex]\[ x_2 = -\frac{5}{3} \][/tex]
[tex]\[ x_2 = -1.6666666666666667 \][/tex]
Thus, the solutions to the quadratic equation [tex]\(3x^2 - x - 10 = 0\)[/tex] are:
[tex]\[ x_1 = 2 \][/tex]
[tex]\[ x_2 = -1.6666666666666667 \][/tex]
The discriminant, [tex]\( \Delta \)[/tex], is 121.
So the solution for the value [tex]\( b \)[/tex] is:
[tex]\[ b = -1 \][/tex]
The given quadratic equation is [tex]\(3x^2 - x - 10 = 0\)[/tex].
For a quadratic equation of the form [tex]\(ax^2 + bx + c = 0\)[/tex], the quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, we have:
- [tex]\(a = 3\)[/tex]
- [tex]\(b = -1\)[/tex]
- [tex]\(c = -10\)[/tex]
Let's first calculate the discriminant, [tex]\(\Delta\)[/tex], which is given by:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \Delta = (-1)^2 - 4(3)(-10) \][/tex]
[tex]\[ \Delta = 1 - (-120) \][/tex]
[tex]\[ \Delta = 1 + 120 \][/tex]
[tex]\[ \Delta = 121 \][/tex]
Now, we'll calculate the two solutions using the quadratic formula:
[tex]\[ x_1 = \frac{-b + \sqrt{\Delta}}{2a} \][/tex]
[tex]\[ x_2 = \frac{-b - \sqrt{\Delta}}{2a} \][/tex]
Substituting the values:
[tex]\[ x_1 = \frac{-(-1) + \sqrt{121}}{2 \cdot 3} \][/tex]
[tex]\[ x_1 = \frac{1 + 11}{6} \][/tex]
[tex]\[ x_1 = \frac{12}{6} \][/tex]
[tex]\[ x_1 = 2 \][/tex]
And for the second solution:
[tex]\[ x_2 = \frac{-(-1) - \sqrt{121}}{2 \cdot 3} \][/tex]
[tex]\[ x_2 = \frac{1 - 11}{6} \][/tex]
[tex]\[ x_2 = \frac{-10}{6} \][/tex]
[tex]\[ x_2 = -\frac{10}{6} \][/tex]
[tex]\[ x_2 = -\frac{5}{3} \][/tex]
[tex]\[ x_2 = -1.6666666666666667 \][/tex]
Thus, the solutions to the quadratic equation [tex]\(3x^2 - x - 10 = 0\)[/tex] are:
[tex]\[ x_1 = 2 \][/tex]
[tex]\[ x_2 = -1.6666666666666667 \][/tex]
The discriminant, [tex]\( \Delta \)[/tex], is 121.
So the solution for the value [tex]\( b \)[/tex] is:
[tex]\[ b = -1 \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.